Effects of Ammonia Stress on Liver Tissue Structure, Enzyme Activities, and Metabolome of Juvenile Largemouth Bass Micropterus salmoides - Decheng Pu; Zhengxi Wang; Jishu Zheng; Peiyuan Li; Xiuli Wei; Dongsheng Li; Lihong Gao; Lin Zhou; Yu Wang (Metabolites)
Background: Ammonia, a ubiquitous contaminant in aquatic ecosystems, poses multifaceted threats to fish species at elevated concentrations. Methods: In order to investigate the toxic effects of chronic ammonia stress on the liver of juvenile Micropterus salmoides, the present experiment was conducted to investigate the differences in changes in liver tissue structure, enzyme activities, and metabolomes after 28 days of ammonia exposure (0, 4, 8, and 16 mg/L). Results: The findings revealed that ammonia exposure induced significant oxidative stress in the liver, manifesting in decreased activities of antioxidant enzymes SOD and GSH-Px, elevated levels of GSH, GST, and MDA, and heightened activities of immune enzymes LZM, ALP, and ACP. An increase in ammonia concentration exacerbated liver tissue damage. Metabolome analysis further unveiled perturbations in liver metabolites of Micropterus salmoides exposed to ammonia, with Ala-His emerging as a potentially pivotal functional substance under chronic stress. Specifically, the 4 mg/L group responded to ammonia toxicity by augmenting GSH and L-Carnosine levels, the 8 mg/L group detoxified via upregulation of L-Glutamine, and the 16 mg/L group mitigated toxicity through the urea synthesis pathway. Conclusions: This research offers preliminary insights into the toxicological responses of Micropterus salmoides under chronic ammonia stress. It is suggested that the duration of ammonia concentration exceeding 4 mg/L in high-density aquaculture should not exceed 7 days.